The development of blowouts and foredunes in the Ilha Comprida barrier (Southeastern Brazil): the influence of Late Holocene climate changes on coastal sedimentation - Sawakuchi, A. O. (2022)
Middle to Late Holocene barriers are conspicuous landforms in southeastern and southern Brazilian regions. The barriers in the coastal zones of northern Santa Catarina, Parana´ and Sa˜o Paulo states (27190– 24000S) are formed mainly by beach ridge alignments and many barriers present foredune and blowout alignments in their seaward portion. The development of these eolian landforms appears to record a regional shift in coastal dynamics and barrier building. In this context, the Ilha Comprida barrier stands out for its well-developed and well-preserved foredunes and blowouts. Based on the presence or not and type of eolian landforms, the Ilha Comprida barrier can be divided seaward into inner, middle and outer units. The inner unit is formed entirely by beach ridges. The middle unit comprises a narrow belt of blowouts (up to 15 m high) aligned alongshore. Blowout lobes pointing NNW are indicative of their generation by southern winds. The outer unit is represented by low ( 1 m high) active or stabilized foredunes and a small transgressive dunefield (w1 km2). Twenty-seven luminescence ages (SAR protocol) obtained for the beach ridges, foredunes, and blowouts of these three units allow definition of a precise chronology of these landforms and calculation of rates of coastal progradation. The inner unit presents ages greater than 1004 88 years. The blowouts of the middle unit show ages from 575 47 to 172 18 years. The ages of the outer unit are less than 108 10 years. Rates of coastal progradation for the inner and outer units are 0.71–0.82 m/year and 0.86–2.23 m/year, respectively. The main phase of blowout development correlates well with the Little Ice Age (LIA) climatic event. These results indicate that southern winds in subtropical Brazil became increasingly more intense and/or frequent during the LIA. These conditions persist to the present and are responsible for the development of the eolian landforms in the outer unit. Thus, barrier geomorphology can record global climatic events. The sensitivity of barrier systems in subtropical Brazil to Late Holocene climate changes was favored by the relative sea level stillstand during this time. Luminescence dating makes it possible to analyze barrier geomorphology during Late Holocene climate changes operating on timescales of a hundred to thousand years. These results improve our knowledge of barrier building and will help in the evaluation of the impact of future climate changes on coastal settings.